Pengaruh Rentabilitas Dan Solvabilitas Terhadap Pengungkapan Tanggung Jawab Sosial Dan Lingkungan Perusahaan Yang Dimoderasi Oleh Ukuran Perusahaan - Hidayatun, Umi; Nugroho, Hendrato Setiabudi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
A company's dedication to sustainable financial development through consideration of social obligations is known as social responsibility. Social and environmental responsibility has become a defining feature of overall business performance evaluation in many foreign countries. Many factors, such as hiring power, solvency, and agency size, have been shown to impact social responsibility disclosure. This study attempts to determine how profitability and solvency influence the disclosure of social and environmental obligations, which is governed by organizational size. The use of secondary data in economic reports is examined quantitatively in this study. The sample for this research was the banking subsector, totaling 45 emitens selected using a purposive sampling technique. From the results of this research, it can be concluded that profitability influences TJSL disclosure. Solvency has no effect on TJSL disclosure. Profitability and solvency partially moderated by company size have no effect on TJSL disclosure. Simultaneously, profitability and solvency influence TJSL disclosure. However, profitability and solvency, which are moderated by company size, have no effect on TJSL disclosure.